PENINGKATAN PENGETAHUAN DAN SIKAP PETERNAK BABI TERHADAP PENYAKIT AFRICAN SWINE FEVER (ASF) DI DESA WAIARA KECAMATAN KEWAPANTE KABUPATEN SIKKA - Keray, Arkadius Suban; Yohanista, Maria; Dede, Matheus Mbele; Siga, Diana Genista (Universitas Nusa Nipa Maumere, 2025)
This study aims to improve farmers' knowledge and attitudes towards African Swine Fever (ASF). This study uses a qualitative descriptive method. The variables measured are the level of farmers' knowledge and attitudes towards ASF. Data analysis was performed using a paired sample t-test with the Statistical Product and Service Solution (SPSS) software version 25. The target of this study was 36 pig farmers, who were sampled using purposive sampling techniques with specific criteria that had been determined, supported by documentation. Pre-tests and post-tests were used to measure the level of knowledge and attitudes towards ASF. The results of the analysis showed an increase in knowledge from the low category by 25%, the medium category by 22.22%, and from the medium category to the high category by 47.22%, and from the high category to the very high category by 11.11%. There was an increase in attitude among 44.44% of farmers who were in the disagree category, 33.33% in the neutral category, an increase in the agree category among 58.33% of farmers, and 27.77% in the strongly agree category. The t-test results showed that the extension activities on ASF affected changes in farmers' knowledge and attitudes toward ASF. Factors influencing the increase were farmer characteristics based on age, education level, and farming experience.